Cross-cultural adaptation and psychometric validation of the Korean version of rehabilitation complexity scale for the measurement of complex rehabilitation needs. Issue 24 (18th June 2021) - Lee, Hoo Young; Park, Jung Hyun; Kim, Tae-Woo
Abstract : Abstract: The aim of this study was to translate and cross-culturally adapt the Rehabilitation Complexity Scale-Extended version 13 (RCS-E v13) to develop the Korean version of the Rehabilitation Complexity Scale (KRCS), and to explore its reliability, and concurrent and construct validity. This research was an observational study of a series of consecutive rehabilitation inpatients who were previously assessed with KRCS and grouped with the Korean rehabilitation patient group version 1.1 (KRPG v1.1). Translation and cross-cultural adaptation of the RCS-E v13 were implemented according to internationally recognized standards. Four hundred thirty inpatients diagnosed with complex neurological or musculoskeletal disabilities were enrolled. Physiatrists were asked to finish the KRCS at admission and to complete a second time with an interval of a minimum of 3 weeks to a maximum of 4 weeks for reliability evaluation. At discharge, the KRCS was completed a third time to explore constructive validity. The Cronbach-α was 0.63. The intraclass correlation coefficient values of the total score, Medical, Nursing, Care, Therapy Disciplines, Therapy Intensity, and Especial Needs domains were 0.86, 0.69, 0.84, 0.83, 0.74, 0.74, and 0.79, respectively ( P  < .01). The scale was repeatable (Spearman rho 0.69–0.86) and correlated strongly with disability measures (Spearman rho 0.37–0.50). Exploratory factor analysis revealed 2 clear factors ("Medical/Nursing" and "Care/Therapy Disciplines/Therapy Intensity/Equipment"). The goodness-of-fit index in the confirmatory factor analysis was 0.87. The KRCS was associated with a higher explanatory power for rehabilitation resources and length of stay than the KRPG v1.1. Our data suggest that the KRCS is a feasible, reliable, and valid tool that is appropriate for the measurement of clinical complexity in Korean intensive rehabilitation units. Further, it may provide case-mix adjustment to improve the rehabilitation delivery system in Korea.